Graphene nanosheets assisted carbon hollow cylinder for high-performance field emission applications - Tripathi, Prashant; Gupta, Bipin Kumar; Bankar, Prashant K.; More, Mahendra A.; Late, Dattatray J.; Srivastava, Onkar Nath (Materials Research Express, 2019)
Electron sources are critical constituents for myriad many electronic applications including electron imaging, mass spectroscopy etc. Here, we report the realization of high-performance field emission from graphene assisted carbon hollow cylinders (Gr-CHCs) composed of multi-stacked radially aligned CNTs. These CHCs have built-in synthesis related Fe nanoparticles (NPs). This engineered nano-structure exhibits excellent field emission properties such as one of the ultra-low turn-on field (0.64V mu m(-1) at 10 mu A cm(-2)), low threshold field (0.74V mu m(-1) at 100 mu A cm(-2)), very high current density (15.49 mA cm(-2) at 1.32V mu m(-1)) which is nearly double the current density obtained in our previous study. High field enhancement factor (0.72. x. 10(4)) with highly stable emission current at 100 mu A was observed for more than 3 hrs at the base pressure of similar to 1. x. 10(-8) mbar. This study suggests an approach to enhance the current density using the proposed innovative nanostructure and forms the basic theme of this communication. Highly efficient and stable field emissions observed are attributed to the geometry of cylinder and the production of the high density of sharp protrusions within the graphene sheets which enhance the local electric field and dramatically enhance field emission. This innovative cylindrical geometry associated with graphene assisted on Fe bearing aligned CNTs along with the periphery of the bulk cylinder provides an easy injection of electrons from the conduction band of CHCs into the vacuum in the presence of an external electric field. The tunability of field emission properties of these CHCs can be easily achieved by tailoring their diameter (10 and 20 mm) and different concentrations of the precursor. This new approach of the graphene assisted cylindrical geometry-based field emitter source provides enormous prospects and demand for next-generation high resolutions display devices.
Keywords: Carbon nanotubes; field emission; graphene assisted carbon hollow cylinder; protrusions